2017
DOI: 10.3390/cryst7100302
|View full text |Cite
|
Sign up to set email alerts
|

Modulating Nucleation by Kosmotropes and Chaotropes: Testing the Waters

Abstract: Abstract:Water is a fundamental solvent sustaining life, key to the conformations and equilibria associated with solute species. Emerging studies on nucleation and crystallization phenomena reveal that the dynamics of hydration associated with mineral precursors are critical in determining material formation and growth. With certain small molecules affecting the hydration and conformational stability of co-solutes, this study systematically explores the effects of these chaotropes and kosmotropes as well as ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 94 publications
0
3
0
Order By: Relevance
“…Additives can influence ion association even without direct binding by modulating the water structure and introducing kosmotropic or chaotropic effects [36,37]. Due to the direct impact on the entropic balance of ion association through the release of hydration waters [38], these effects can increase or weaken ion-ion and/or ion-additive interactions [39], providing additional means to tune the strength of corresponding intermolecular interactions.…”
Section: Adsorption Of Free Ions and Pre-nucleation Clustersmentioning
confidence: 99%
“…Additives can influence ion association even without direct binding by modulating the water structure and introducing kosmotropic or chaotropic effects [36,37]. Due to the direct impact on the entropic balance of ion association through the release of hydration waters [38], these effects can increase or weaken ion-ion and/or ion-additive interactions [39], providing additional means to tune the strength of corresponding intermolecular interactions.…”
Section: Adsorption Of Free Ions and Pre-nucleation Clustersmentioning
confidence: 99%
“…External modulators of solvation also regulate the formation of PNCs from nanoscopic solute precursors. For instance, PNC‐associated ions and organic molecules presenting higher hydration contents hinder the dehydration of the ionic species, thereby enhancing the supersaturation levels required for particle nucleation ,. Thus, the nucleation process cannot be deconstructed to a simple aggregation‐based size evolution from individual ions to particles, but also is ingrained by the configurational and molecular nature of solute precursors in relation to their environment, (Figure a–c).…”
Section: On the Nature Of Materials Precursorsmentioning
confidence: 99%
“…A further evidence for the important role of water in the formation of PNCs could be found by the influence of cosmotropes and chaotropes species on the PNCs. These substances modify the water structure within the solution, thereby influencing the hydration of PNCs and leading to changes in their stability. , …”
Section: Understanding and Controlling C–s–h Nucleationmentioning
confidence: 99%
“…These substances modify the water structure within the solution, thereby influencing the hydration of PNCs and leading to changes in their stability. 165,166 Once the binodal limit is overcome and liquid nanodroplets nucleated, the water mobility decreases due to the reduced motion of the molecules in the dense nanodroplets compared to the surrounding diluted solution phase. 163 Simulations have shown that the decrease in the PNC dynamics upon the nucleation of the liquid nanodroplets can be understood as an increase in the coordination number relative to the initial chain-like structures.…”
Section: Two-step Nucleationmentioning
confidence: 99%